2017
DOI: 10.1038/cddis.2016.443
|View full text |Cite
|
Sign up to set email alerts
|

Continued 26S proteasome dysfunction in mouse brain cortical neurons impairs autophagy and the Keap1-Nrf2 oxidative defence pathway

Abstract: The ubiquitin–proteasome system (UPS) and macroautophagy (autophagy) are central to normal proteostasis and interdependent in that autophagy is known to compensate for the UPS to alleviate ensuing proteotoxic stress that impairs cell function. UPS and autophagy dysfunctions are believed to have a major role in the pathomechanisms of neurodegenerative disease. Here we show that continued 26S proteasome dysfunction in mouse brain cortical neurons causes paranuclear accumulation of fragmented dysfunctional mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…When we investigated if p62 modulated this phenotype, we indeed found a synergistic toxic effect of mutant LRRK2 and p62 expression, dependent on Thr138 (Figure 9). It is possible that, in this context, overexpressed hyperphosphorylated p62, co-expressed with G2019S-LRRK2, fails to activate the Nrf2 cytoprotective pathway similar to that recently reported in cultured neurons in which elevated levels of phosphorylated p62 (at Ser351) are observed following proteasome inhibition [126]. In fact, it was recently shown that up-regulating Nrf activity decreased LRRK2 neuronal toxicity [79].…”
Section: Discussionsupporting
confidence: 66%
“…When we investigated if p62 modulated this phenotype, we indeed found a synergistic toxic effect of mutant LRRK2 and p62 expression, dependent on Thr138 (Figure 9). It is possible that, in this context, overexpressed hyperphosphorylated p62, co-expressed with G2019S-LRRK2, fails to activate the Nrf2 cytoprotective pathway similar to that recently reported in cultured neurons in which elevated levels of phosphorylated p62 (at Ser351) are observed following proteasome inhibition [126]. In fact, it was recently shown that up-regulating Nrf activity decreased LRRK2 neuronal toxicity [79].…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have revealed that mitochondrial impairment occurs soon after proteasome inhibition (Maharjan et al, 2014). In fact, continued proteasome dysfunction in mouse brain cortical neurons inhibited the degradation of ubiquitylated mitochondrial proteins and led to the accumulation of dysfunctional mitochondria (Ugun-Klusek et al, 2017). Misfolded proteins such as mutant SOD1 have also been shown to interact with mitochondrial proteins and translocate into the mitochondrial intermembrane space and mitochondrial matrix, where they accumulate and induce mitochondrial dysfunction (Vijayvergiya et al, 2005;Jaarsma et al, 2001;Ruan et al, 2017;Igoudjil et al, 2011;Fischer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, plenty of evidence exists linking alterations of either autophagy or UPS with the aggregation, spreading and toxicity of so called prionoids, including α-syn, Aβ, tau, huntingtin, SOD1, TDP-43 and FUS [19,29,[52][53][54][55][56][57][58][59][60]. Albeit being both autophagy and UPS implicated in the clearance of the above-mentioned proteins, recent biochemical and morphological studies have added to this scenario, focusing on the cross-talk between these two systems [61][62][63][64][65][66][67][68][69][70][71][72][73]. In fact, a coordinated, either synergistic or compensatory interplay occurs between autophagy and the UPS, which has attracted the attention of many investigators while challenging the traditional view of two segregated and independent degradation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Besides sharing prion-like protein substrates, autophagy and UPS converge at both biochemical and morphological levels [61][62][63][64][65][66], though the functional significance of such an interplay remains to be fully elucidated. A growing number of biochemical pathways are being shown to operate at the crossroad between autophagy and UPS, orchestrating the specificity and magnitude of the two degradation systems for effective protein homeostasis [61][62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Introductionmentioning
confidence: 99%